Dual-resonance concurrent oscillator. (April 2018) - Jang, Sheng-Lyang; Kang, Chih-Chiang; Wang, Huan-Chun; Juang, Miin-Horng
Abstract: This paper studies a new dual-band CMOS class-C voltage-controlled oscillator (VCO). The oscillator consists of a dual-resonance LC resonator in shunt with two pairs of capacitive cross-coupled nMOSFETs. The proposed oscillator has been implemented with the TSMC 0.18 μm CMOS technology, and it shows a frequency tuning range with two frequency bands and a small tuning hysteresis is measured. The oscillator can generate differential signals at 2.4 GHz and 6.9 GHz and it also can generate concurrent frequency oscillation while the circuit is biased around the bias with frequency tuning hysteresis. With the supply voltage of VDD  = 1.1 V, the VCO-core current and power consumption of the oscillator are 2.90 mA and 3.19 mW, respectively. The die area of the class-C oscillator is 0.9 × 0.97 mm 2 . Overvoltage stress is applied to the oscillator, measurement indicates the concurrent oscillation is sensitive to overvoltage stress. Highlights: A dual-band CMOS voltage-controlled oscillator is proposed. The oscillator shows dual-band tuning range with a hysteresis loop around the high-low band transition. Biased around the hysteresis loop, the oscillator outputs high- and low-band frequency signals concurrently. The concurrent oscillation is sensitive to hot-carrier stress.